Synthesis, characterization, anti-microbial and anti-fungal activity studies of four novel 2-aminopyridine and 2,4-dichloro-5-sulfamoylbenzoic acid salts and their Cu(II) complexes - halil ilkimen; Aysel Gülbandılar (Kuwait Journal of Science)
Four novel proton transfer compounds (1-4) obtained between 2-aminopyridine (1), 2-amino-4-methylpyridine (2), 2-amino-5-methylpyridine (3), 2-amino-6-methylpyridine (4) and 2,4-dichloro-5-sulfamoylbenzoic acid (Hsba) and their Cu(II) complexes (6-10) have been synthesized. The structures of powdery salts (1-4) and complexes (6-10) have been suggested by spectral (1H-NMR, FT-IR and UV–Vis), elemental analysis, AAS, molar conductivity and magnetic susceptibility techniques of 6-10 have also been reported. The structures of metal complexes (6-10) were observed octahedral according to spectroscopic analysis results. Additionally, anti-microbial and anti-fungal activities of all compounds have been tested against Escherichia coli (ATCC 25922) (Gram negative), Enterococcus faecalis (ATCC 29212) (Gram positive), Staphylococcus aureus (ATCC 29213) (Gram positive), and Candida Albicans (ATCC 14053) (yeast), Candida parapisilosis (ATCC 22019) (yeast), and Candida krusei (ATCC 6258) (yeast). The results were comparisoned with the antibiotics, Fluconazole as anti-fungal agent and Cefepime, Levofloxacin, Vancomycin as anti-microbial agents. Activity against all compounds bacteria and yeasts was observed. Therefore, all compounds may be utilized for the synthesis of new anti-microbial and anti-fungal. Compounds with the best activity are 2 (15.60 μg/mL) for S. aureus, 2, 8 and 11 (31.25 μg/mL) for E. Faecalis, 2a5mp, 1, 2 and 9 (31.25 μg/mL) for E. Coli, Cu(OAc)2.2H2O, 1, 2 and 9 (31.25 μg/mL) for C. Parapsilosis, Hsba (15.60 μg/mL) for C. Albicans and Hsba and 8 (31.25 μg/mL) for C. Krusei.